The Global Film Market Transformation in the Post-Pandemic Era: Production, Distribution and Consumption - Qiao Li; David Wilson; Yanqiu Guan (Routledge, 2023)
This book reviews the development and performance of the global film industry during the COVID-19 pandemic and examines new trends in film production, distribution and consumption through a global lens. The COVID-19 pandemic has had a substantial impact on the global film industry since the beginning of 2020. There has been significant transformation in terms of film production, distribution and consumption. Hollywood, like many national cinemas across the globe, has suffered the most significant impact at all levels: the interruption of new film productions, shutdowns of movie theatres in many countries and delays in the release of new films, among them. Many movies made for cinemas were forced to move from release in theatres to various streaming platforms, and nontraditional production companies continued to grow their market share. This book places the global film industry in a post-Pandemic context. It provides detailed analyses of specific systems of film production, distribution and consumption in national cinemas, as well as in Hollywood, while also engaging with the key theoretical and methodological questions from the film studies literature. This volume is a critical reference for students and scholars of film studies and general readers who are interested in the new trends and transformation of the global film industry in a post-Pandemic era.
Keywords: 320; Film Studies; Global Film Industry; Post-Pandemic Film Market